Five-year outcomes following PCI with DES versus CABG for unprotected LM coronary lesions: meta-analysis and meta-regression of 2914 patients - Michel Pompeu Barros de Oliveira Sá (Revista Brasileira de Cirurgia Cardiovascular/Brazilian Journal of Cardiovascular Surgery, 2013)
OBJECTIVE: To compare the safety and efficacy at long-term follow-up of coronary artery bypass grafting (CABG) with percutaneous coronary intervention (PCI) using drug-eluting stents (DES) in patients with unprotected left main coronary artery (ULMCA) disease.METHODS: MEDLINE, EMBASE, CENTRAL/CCTR, SciELO, LILACS, Google Scholar and reference lists of relevant articles were searched for clinical studies that reported outcomes at 5-year follow-up after PCI with DES and CABG for the treatment of ULMCA stenosis. Five studies (1 randomized controlled trial and 4 observational studies) were identified and included a total of 2914 patients (1300 for CABG and 1614 for PCI with DES).RESULTS: At 5-year follow-up, there was no significant difference between the CABG and PCI-DES groups in the risk for death (odds ratio [OR] 1.159, P=0.168 for random effect) or the composite endpoint of death, myocardial infarction, or stroke (OR 1.214, P=0.083). The risk for target vessel revascularization (TVR) was significantly lower in the CABG group compared to the PCI-DES group (OR 0.212, P<0.001). The risk of major adverse cardiac and cerebrovascular events (MACCE) was significantly lower in the CABG group compared to the PCI-DES group (OR 0.526, P<0.001). It was observed no publication bias about outcomes and considerably heterogeneity effect about MACCE.CONCLUSION: CABG surgery remains the best option of treatment for patients with ULMCA disease, with less need of TVR and MACCE rates at long-term follow-up.